Application of the pulsed electric field to release bound phenolics in sorghum flour and apple pomace. (June 2016) - Lohani, Umesh C.; Muthukumarappan, K.
Abstract: The mild intensity pulsed electric field (PEF) was studied to release bound phenolics in sorghum flour (SF) and apple pomace (AP). In this study, SF and AP, naturally fermented at optimized conditions, were treated at different flour to water ratios (FWRs) of 10, 27.5, 45% (w/v) and 5, 8.75, 12.5% (w/v), respectively. In addition, three levels of PEF electric field intensity (EFI) as 1, 2 and 3 kV/cm were used to treat SF and AP for the treatment time of 500, 875 and 1250 μs. Both the treated samples were analyzed for total phenolic content (TPC), antioxidant activity (AA) and phenolic characterization. For SF, optimized conditions were determined as 45% (w/v) FWR, 2 kV/cm EFI and 875 μs treatment time, while these values were 12.5% (w/v) FWR, 2 kV/cm EFI and 500 μs for AP. At these conditions, TPC and AA of SF were 24.8% and 33.9%, respectively higher than the control SF, while for AP, these numbers were observed as 37.4% and 86%, respectively. The study suggests that PEF treated SF and AP may be very useful for the preparation of processed foods with the increased levels of phenolic antioxidants. Industrial relevance: Sorghum, millets and fruit or vegetable by-products contain high amounts of flavonoids and phenolic acids among other bioactive compounds. Results explicate that the application of a PEF treatment following the fermentation could improve the phenolic antioxidants in the sorghum flour and apple pomace. Consequently, this technology could be used in the food industry to enhance the healthy properties of millets and other by-products prior to further processing like mild extrusion or baking. Also the use of the mild intensity pulsed electric field has the benefit of minimizing any damage to the other nutrients of any product. Highlights: Mild intensity PEF can release bound phenolics in sorghum flour and apple pomace. Potential use of fermentation followed by PEF treatment Antioxidant activity increased by 34% and 86% in sorghum flour and apple pomace. MIPEF can be a applied to similar foods to improve phenolic antioxidants.